Is Climate Change Still a Spatially Distant Threat? An Empirical Study of Students' Perception of Spatial Climate Change Impact - Kerscher, Josef; Schubert, Jan Christoph; Gölitz, Dietmar; Velling, Hanna; Höhnle, Steffen (Journal of Geography Education, 2025)
Multiple empirical studies suggest that students perceive climate change as a distant spatial phenomenon. The resulting psychological distance may hinder sustainable action. Given a decade of intense climate debates, the Fridays-for-Future movement and an increase in extreme weather events, this survey-based study (n = 6,232) examines whether Bavarian students now perceive their local environment to be more affected by climate change. The results surprisingly show persistent distance perception, with the perceived impacts increasing from local to global scales. Students continue to view climate change as a global phenomenon, which underlines the need to focus on local climate change impacts in climate education.
Keywords: climate change, perceived impact, spatial bias, climate education, students